of, and, on, the, for, that, is Legal Efforts of Banks and Buyers on Discharging the Collateral Object for Auction that is Still Occupied - Marina Ayusta Amindya Putri (Hang Tuah Law Journal, 2020)
Credit is the banking service that would require the colletral agreement of pledge assets to give the creditor a sense of security in case the debtor would not be able to pay the loan based on the agreement. After it is proven that the debtor could not pay the amount agreed on the agreement, then the pledge assets will go for a public auction by the creditor. The provit of the auction then will be used to pay off the amount of money that the debtor owed to the creditor. For instance, the debtor would need to walk away from the pledge assets including their house and other assets in connection to the loan but more often than not, the debtor choose to stay in the buildings they signed as the pledge assets for the amount of money they owe and refuse to walk away from it. Though legally, the buildings that are being written as the pledge assets are essentially forefeitable for the auction to be bought by the buyer for the profit of the creditor. Once they are sold on the auction, they are the property of the buyers instead of the owner who owed the creditor. Thus, this paper questions about the legal steps that can be taken by the creditor and buyers on the emptying of the buildings as the object of collateral based on legal facts, literature, and the law. The paper aims to give a solution on how the object collateral dispute can be solved and the buyers can get what they bough on the public auction.